Controlling of Profit Distribution in Dividend Policy Shaping - N. V. Gryzunova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The Russian stock exchange resumes its functions after a temporary break due to the special operation in Ukraine.  A lot of companies tend to modify their finance behavior, for instance, methods of finance control are rather topical today, as both cash flow lines and approaches to dividend policy shaping are changing. The goal of the research is to identify dependence between dividend policy, key parameters of company work and investment behavior of the population. Today extra drivers of economic growth and tools of market stabilization are necessary. According to the theory of company value corporations would increase their capitalization and thus raise shareholders’ profits, while now shareholders are interested in developing a dividend portfolio, whose profits are comparable with deposits and investing into bonds. Finance behavior of market entities has altered, as des-intermediation is going down, further differentiation of tax rates took place, tax burden on investors (both legal entities and individuals) was optimized and investors were differentiated by finance groups with provision of adequate dividends for each group. The author points out that due to serious changes on finance market we need controlling of profit distribution and corporate dividend flows, as well as timely revealing of deviations in cash flows.